Theoretical Analysis for Proton Conductivity at Sigma 3 Tilt Grain Boundary of Barium Cerate - Yang, Jin-Hoon; Kim, Byung-Kook; Kim, Yeong-Cheol (AMER SCIENTIFIC PUBLISHERS, 2015)
We theoretically analyzed proton conductivity at the Sigma 3 tilt grain boundary (GB) of barium cerate using density functional theory. Two types of positively charged defects, a proton and an oxygen vacancy, were segregated at the GB with segregation energies in the range of -0.36 similar to-0.52 and -0.17 similar to-0.30 eV, respectively. Segregated defects at the GB built up an electrostatic potential of 0.41 V at 600 K. The segregated proton at the GB required energy barriers in the range of 0.66 similar to 0.86 eV in order to migrate across the GB. Based on the electrostatic potential and energy barriers, proton conductivities in bulk, and at the GB of barium cerate, were calculated and compared with experimental values.
Keywords: TOTAL-ENERGY CALCULATIONS; WAVE BASIS-SET; SPACE-CHARGE; BAZRO3; DIFFUSION; CERAMICS; OXIDES; BACEO3; GD